Risk factors for the first and second inappropriate implantable cardioverter-defibrillator therapy - Nishii, Nobuhiro (Int J Cardiol Heart Vasc, 2021)
INTRODUCTION: Various risk factors for the first inappropriate implantable cardioverter-defibrillator (ICD) therapy event have been reported, including a history of atrial fibrillation/atrial flutter (AF/AFL), younger age, and multiple zones. Nonetheless, which factors are concordant with real-world data has not been clarified, and risk factors for the second inappropriate ICD therapy event have not been well examined. This study aimed to clarify the risk factors for the first and second inappropriate ICD therapy events. METHODS: We conducted a post-hoc secondary analysis of data from a multicenter, prospective observational study (the Nippon Storm Study) designed to clarify the risk factors for electrical storm. RESULTS: The analysis included data from 1549 patients who received ICD or cardiac resynchronization therapy with defibrillator (CRT-D). Over a median follow-up of 28 months, 293 inappropriate ICD therapy events occurred in 153 (10.0%) patients. On multivariate Cox regression analysis, the risk factors for the first inappropriate ICD therapy event were younger age (hazard ratio [HR], 0.986; p = 0.028), AF/AFL (HR, 2.324; p = 0.002), ICD without CRT implantation (HR, 2.377; p = 0.004), and multiple zones (HR, 1.852; p = 0.010). “No-intervention” after the first inappropriate ICD therapy event was the sole risk factor for the second inappropriate ICD therapy event. CONCLUSIONS: Risk factors for the first inappropriate ICD therapy event were similar to those previously reported. Immediate intervention after the first inappropriate ICD therapy event could reduce the risk of the second inappropriate event.